Turkey and Russia: The logic of conflictual cooperation - Daria Isachenko (Stiftung Wissenschaft und Politik (SWP), 2021)
Relations between Turkey and Russia are a puzzle to many in the West. How sustainable is the relationship? What is it grounded on? And what can the West learn from it? Central to the relationship is its bilateral nature. Relations between Ankara and Moscow are based on the mutual recognition of security interests. The resulting dynamics have shaped Turkish-Russian cooperation since the 1990s and can be observed in the current partnership in Syria. Mutual regard for the other's security concerns is facilitated by the prospect of collaborative projects that promise greater advantages than continued conflict. Trust is of secondary importance, as is the quality of personal relations between the Turkish and Russian presidents. More important is the interdependence between Russia and Turkey. The potential for confrontation or cooperation between Ankara and Moscow in regional conflicts depends on current priorities rather than past rivalries. The form and extent of their collaboration are determined not by which side of the conflict they are on, but by their respective motives.
Keywords: 320